Pengetahuan dan sikap ibu tentang kebersihan gigi dan mulut pasca ceramah pendidikan kesehatan gigi disertai diskusi kelompok atau disertai hands on - Agusthinus Wali; Sri Widiati; Niken Widyanti Sriyono (Majalah Kedokteran Gigi Indonesia, 2016)
ABSTRACT: The difference increased knowledge and attitudes of mothers about oral hygiene through dental health education lecture with discussion groups and lectures with hands on. Dental health education will be more effective when started from the family by teaching the mothers about the importance of oral health maintenance. This study aims to determine the difference in the increased knowledge and the attitudes of mothers about oral hygiene through dental health education lecture with discussion groups and lectures with hands on. This study was a quasi-experimental design with pretest and post-test group design. The subjects of research were 95 mothers of children aged 6-8 years who met the inclusion criteria and divided into two groups. Group I in PPA IO-497 Benjamin Oebufu, Kupang (53 subjects) were given a lecture with discussion groups and group II in PPA IO-495 Alfa Omega Bakunase 2, Kota Kupang with total of 42 subjects were given a lecture with hands on. Measuring tool was a questionnaire. The analysis of data using Statistic Program for Social Science (SPSS) for a different test testing the T-test for normal distribution of data, while the Mann-Whitney test and the Wilcoxon Signed Rank test were for abnormal distribution data. The initial analysis on knowledge and attitudes obtained some comparable results in which there were no differences between treatment groups I and II (p > 0.05). The results of the analysis of mean differences between groups on post-test 1 and 2 showed some significant differences knowledge and attitudes in the treatment group II of the treatment group I (p < 0.05). The results of the analysis of the average increase showed the increased knowledge and attitudes were significant in both treatment groups. Delta analysis results from pre-test to post-test 1 and pre-test to post-test 2 showed the treatment group improved knowledge and attitudes II is higher than in the treatment group I (p < 0.05). Dental health education using lecture with hands on increased knowledge and attitudes about the subject of oral hygiene of the a lecture with discussion groups.   ABSTRAKPenelitian ini bertujuan untuk mengetahui perbedaan peningkatan pengetahuan dan sikap ibu tentang kebersihan gigi dan mulut melalui pendidikan kesehatan gigi metode ceramah disertai diskusi kelompok dan ceramah disertai hands on. Penelitian dilakukan pada subjek penelitian sebanyak 95 ibu dari anak umur 6-8 tahun yang memenuhi kriteria inklusi dan terbagi dalam dua kelompok. Kelompok perlakuan I di PPA IO-497 Benyamin Oebufu, Kota Kupang sebanyak 53 subjek diberikan ceramah disertai diskusi kelompok dan kelompok II di PPA IO-495 Alfa Omega Bakunase 2, Kota Kupang sebanyak 42 subjek diberikan ceramah disertai hands on. Alat ukur dalam penelitian adalah kuesioner. Analisis data menggunakan Statistik Program for Social Scince (SPSS) untuk uji beda yaitu uji T-test untuk data distribusi normal, sedangkan Mann-Whitney test dan Wilcoxon Signed Ranks test untuk data distribusi tidak normal. Hasil analisis perbedaan rerata antar kelompok pada post-test 1 dan 2 terdapat perbedaan pengetahuan dan sikap yang signifikan pada kelompok perlakuan II lebih tinggi dari pada kelompok perlakuan I (p < 0,05). Hasil analisis rerata peningkatan terdapat peningkatan pengetahuan dan sikap yang signifikan pada kedua kelompok perlakuan. Hasil anal isis delta dari pre-test ke post-test 1 dan pre-test ke post-test 2 menunjukkan pada kelompok perlakuan II peningkatan pengetahuan dan sikap lebih tinggi dari pada kelompok perlakuan I (p < 0,05). Pendidikan kesehatan gigi dengan metode ceramah disertai hands on lebih meningkatkan pengetahuan dan sikap subjek tentang kebersihan gigi dan mulut dari pada metode ceramah disertai diskusi kelompok.